Perencanaan Produksi Kantong Sampah Plastik Menggunakan Metode Linear Programming Di PT Kharisma Plastik Indo - Dwiza Adyasa, Nidhya; Hidayah, Nur Yulianti (Metris: Jurnal Sains dan Teknologi, 2024)
PT Kharisma Plastik Indo (PT KPI) is a company that produces recycled plastics and cassava-based plastics. The main product produced by PT KPI is trash bags which have 2 variants, namely black and green. Currently, the company is faced with the problem of stacking finished goods in storage. In carrying out the production, the company uses daily targets without looking at historical sales data. This study aims to estimate the number of trash bag production using the Linear Regression forecasting method, make aggregate production planning using the Linear Programming method, and disaggregate to determine production schedule of each variant with the percentage of sales method. Forecasting demand for trash bag in October 2022 – February 2023 respectively are 10,061 kg, 9,844 kg, 9,627 kg, 9,410 kg and 9,193 kg. The aggregate planning resulted the total production of trash bags in October - December 2022 respectively are 3,999 kg in normal hours, 9,729 kg in normal hours and 115 kg in overtime, and 9,627 kg in normal hours. January – February 2023 in normal hours are 9,410 kg and 9,193 kg. The disaggregation obtained the trash bag production schedule for October 2022 – February 2023 respectively are 2,131 kg of the black and 1,868 kg of the green, 5,245 kg of the black and 4,599 kg of the green, 5,129 kg of the black and 4,498 kg of the green, 5,014 kg of the black and 4,396 kg of the green, and 4,898 kg of the black and 4,295 kg of the green.